Observation of Arteria Thyroidea Ima in Bangladeshi People: A Postmortem Study - Banna, Fakhrul Amin Mohammad Hasanul; Sultana, Zakia (Journal of Enam Medical College, 2018)
Background: The thyroid is a brownish red, earliest endocrine gland in mammals. The blood flow to the thyroid gland is very high. The thyroid derives its arterial blood supply from three vessels; of these, the superior and inferior thyroid arteries are fairly constant. The third artery, the thyroidea ima, is an inconstant vessel. Diseases of thyroid may need surgical intervention.This study aims to find out the presence of the arteria thyroidea ima and its origin in Bangladeshi people. Objective: The present study was carried out on considering the day-to-day growing clinical importance, and insufficient morphological data and arterial supply by thyroidea ima artery of thyroid gland and possible geographical variations in Bangladeshi people. This study will also help in minimizing complications of thyroid surgery and tracheostomy. Materials and Methods: This descriptive crosssectional study was carried out on 54 postmortem human thyroid glands collected from individuals aged 5 to 65 years. Thyroid glands were collected from unclaimed dead bodies autopsied in the morgue of Sylhet M. A. G. Osmani Medical College, Sylhet. The collected specimens were examined by careful gross dissection method. Results: Thyroidea ima artery was present in 3.70% cases, which originated equally from brachiocephalic trunk and arch of aorta. Conclusion: Presence of this artery must be searched out during thyroid surgery and tracheostomy. J Enam Med Col 2018; 8(1): 25-28